PROSES BERPIKIR SISWA SMP DALAM MEMECAHKAN MASALAH MATEMATIK DITINJAU DARI GAYA KOGNITIF FIELD DEPENDENT DAN FIELD INDEPENDENT - Nur Alifah; Usman Aripin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to describe the thinking process of junior high school students in solving mathematical problems reviewed based on cognitive style field dependent and field independent. The method used in this research is descriptive qualitative research method, while the method of data retrieval is test and interview. The study conducted on the VII grade students of SMPN 2 Marga Asih.The subjects of the study were 2 students from junior high school consisting of 1 students with cognitive field dependent and 1 student style with an independent cognitive field. The results showed that there were significant differences between the two subjects in processing information, that was the subject of FI understand the problem better when compared with the subject of FD. Because if processing information was not stored properly, it will be very influential in the next step.